The possible positive effects of physical exercise on the global motion perception aging: the cognitive mechanism - Liang, Ziping; Zhang, Lei; Wang, Pengpeng; Zhang, Yuping; Xia, Yaoyuan; Jin, Hua (Frontiers in Psychology, 2024)
Background Sensitivity to global motion perception (GMP) decreases gradually with age, and the mechanism to effectively alleviate its aging process is still unclear. This study aimed to examine the impact and mechanism of exercise on GMP aging. Methods This study adopted the global motion direction discrimination task and used motion coherence thresholds to assess GMP sensitivity. It adopted the perceptual template model (PTM) to fit the GMP processing efficiency. Results The threshold for the elderly group with no exercise was higher than that of the elderly group with exercise, while the threshold of the latter was higher than that of the youth group. The results of the model fitting showed that both models, Aa and Af, corresponding to the elderly group with exercise and the elderly group with no exercise, respectively, were the best-fitted models when compared with that of the youth group. Compared to the elderly group with no exercise, models Aa and Af, were the best-fitted models. Conclusion These results showed that good exercise habits might have a certain degree of positive effect on GMP aging, by lower their internal additive noise (Aa), and improve the ability to eliminate external noise (Af).